Effect of herbicidal weed management and vermicompost on yield attributes and yield of clusterbean Cyamopsis tetragonoloba (L.) Taub under southern region of Rajasthan - Harish Kumar Bijarnia; Arvind Verma; Shankar Lal Bijarnia; M.K. Kaushik; Shankar Lal Sunda; Monika Choudhary (Annals of Agricultural Research, 2024)
A field experiments consisting different weed management practices and levels of vermicompost was tried at Udaipur during kharif 2020 and 2021. The experiment was laid out in factorial randomized block design with three replications. Results revealed that pre-emergence application of pendimethalin + imazethapyr (RM) 750 g ha-1 fb hand weeding at 40 DAS showed prominent yield attributes and yield viz. seed, straw and biological yield and harvest index during both research work. Application of vermicompost 5 t ha-1 also observed significantly higher yield attributes viz. pods plant-1 (29.41), seeds pod-1, (6.65), pod length (5.72), 1000 seed weight (24.66 g), seed (1161 kg ha-1), haulm (2390 kg ha-1) and biological (3552 kg ha-1) yield and harvest index (32.32%) of clusterbean over control. Therefore, clusterbean should be fertilized with vermicompost 5 t ha-1 and weeds must be controlled with pendimethalin + imazethapyr (RM) 750 g ha-1 PE fb hand weeding at 40 DAS.